Strategi Komunikasi Interpersonal Guru dan Murid dalam Kegiatan Pembelajaran PAUD TK Dharma Wanita Persatuan Baturube - Mahmud Mahmud; Fatmawati Fatmawati; Yulinar Yulinar (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
The purpose of this study is to find out how interpersonal communication strategies of teachers and students in learning activities in PAUD TK Dharma Wanita Persatuan Baturube, North Bungku District, North Morowali Regency. The research method used is qualitative research with a descriptive abbreviation which aims to provide an overview of the extent of teacher and student interpersonal communication strategies in learning activities in PAUD TK Dharma Wanita Persatuan Baturube District. North Bungku, North Morowali Regency. The data analysis technique used is triangulation which consists of data reduction, data presentation, and conclusion drawing. The results showed that the interpersonal communication strategies used in PAUD Dharma Wanita Persatuan Baturube, among others, were a. Approach b. Storytelling, c. Play, d. Questions and Answers, e. and Lectures. Thus, interpersonal communication strategies between teachers and students in providing educational materials in teaching and learning activities at PAUD Dharma Wanita Persatuan Baturube are considered effective when communication planning is carried out according to obligations in accordance with the regulatory system adopted by PAUD Dharma Wanita Persatuan Baturube and reaches an understanding for the realization of common goals and goals..